Chewing Gum, Acetaminophen, and Green Tea Effect in Reducing Pain After Orthodontic Appliance Placement - Elvina Elvina; Joko Kusnoto; Himawan Halim; Boedi Oetomo Roeslan (Scientific Dental Journal, 2018)
Background: Pain is a common problem encountered after fixed orthodontic appliance placement. Pain from orthodontic treatment can come from ischemia, inflammation, and edema in the periodontal ligaments that were depressed. Objectives: To determine whether there are differences in the pain reduction associated with chewing gum, taking acetaminophen, and gargling green tea after fixed orthodontic appliance placement. Methods: This study is a quasi-experiment with a controlled randomized post-treatment approach using 40 subjects. The subjects were consecutively selected and then randomly assigned into four equal groups: a group assigned to chewing gum, a group assigned to take acetaminophen, a group assigned to gargle green tea, and a control group. The level of pain was measured using a Visual Analogue Scale (VAS). A one-way ANOVA test was used to analyse differences between the groups. Results: The VAS scores of the chewing gum and acetaminophen groups were lower than the green tea and control groups. At 24 hours after fixed orthodontic appliance placement, only the chewing gum group reported a decrease in the amount of pain experienced. Overall, the chewing gum group reported the lowest pain scores compared to other groups. However, there was no overall statistically significant difference between the chewing gum and acetaminophen group (p>0.05). Additionally, there was no statistically significant difference in the amount of pain reduction experienced by the green tea group and the control group (p>0.05). There was a significant difference in the amount of pain reduction reported between the chewing gum or acetaminophen groups and the green tea group (p<0.05). Conclusion: There was no significant difference between chewing gum and taking acetaminophen in the amount of pain reduction experienced after fixed orthodontic appliance placement, but gargling with green tea was found to be significantly less effective in reducing pain. Because it has fewer side effects, chewing gum may be a more preferable alternative to taking acetaminophen to reduce pain after fixed orthodontic appliance placement.